Penerapan Assesmen Uraian Dalam Meningatkan Kemampuan Matematika Siswa di SDIT Alam IKM Al-Muhajirin - Nurhalizah; Istiyati Mahmudah (Tadris Matematika, 2024)
This research discusses the application of descriptive assessments in improving students' mathematical abilities at SDIT Alam IKM AL-Muhajirin. The main aim of this research is to understand how to improve descriptive assessments in students' mathematical abilities and to explore an in-depth understanding of the impact of using descriptive assessments to improve students' mathematical abilities. This research uses qualitative research. This research technique involves collecting data through in-depth interviews with mathematics teachers in high classes related to the implementation of essay question assessments. The results of the research show that the application of essay question assessments makes a positive contribution to students' understanding of mathematical concepts. The teacher said that understanding the use of high level description questions (Hots) can encourage students to think critically and develop a deeper understanding. Apart from that, the essay question assessment also encourages the development of students' critical thinking and mathematical communication skills. The results of this research provide in-depth insight into the benefits of assessing descriptive questions in the context of SDIT Alam IKM Al-Muhajirin. The implication of this research is that a qualitative approach in implementing essay question assessment can provide a deeper understanding of changes in students' understanding and its positive impact on mathematics learning. In the world of education, student assessment is the process of collecting information that is used to make decisions about students, curricula, programs, schools, and educational policies.